The News of Governor Candidacy on 2017 Banten Gubernatorial Election in Radar Banten (Study of Media Content Analysis) - Achmad Nashrudin Priatna (Universitas Muhammadiyah Tangerang, 2018)
This study aims to find out how Radar Banten reports on the practice of political economy and how the neutrality and professionalism of Radar Banten in the Banten Gubernatorial Election 2017. As long as the 2017 Banten Gubernatorial Election contestation takes place, Radar Banten, as with other local media, play a role in disseminating various news related to the contestation. This research is qualitative research with the method of framing analysis. The data analysis method used in this study is the analysis of media political economy, content analysis, framing analysis and discourse analysis. The results of this study showed that the news presented by Radar Banten tended to favor one of the candidates. This also shows that Radar Banten is not neutral and unprofessional in presenting the news related to the Banten Gubernatorial Election 2017.